Managerial Instructional Communication Strategy On The Quality Of Graduates Of Administrator Leadership Training At The Human Resources Development Agency Of North Sumatra Province - Muhammad Kahfi; Syukur Kholil; Nurussakinah Daulay (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to analyze the instructional communication strategies that training managers apply to the quality of graduate administrator leadership training at the North Sumatra Provincial Human Resources Development Agency. The qualitative research method was conducted by in-depth interviews with training managers, instructors, and trainees. The study results show that the training manager implements various instructional communication strategies, including using learning methods that are responsive to the participants' learning styles. The application of communication technology is also an integral part of this strategy, providing diversity in learning approaches. It was found that two-way interaction between managers and trainees significantly increased participants' understanding and engagement. This research contributes to a further understanding of the importance of instructional communication strategies in the context of administrator leadership training. It guides the development of training programs in similar institutions.Keywords:Instructional Communication; Quality of Graduates; Administrator Leadership Training